Analisis Kebijakan Kepala Sekolah Dalam Peningkatan Kompetensi Guru dan Mutu Pembelajaran IPAS di SD Inpres Tamannyeleng Kecamatan Barombong Kabupaten Gowa - Sahriani, Sahriani; Rahman, Nawir; Hartini, Hartini (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the policy of school principals in improving teacher competence and the quality of science and technology learning at SD Inpres Tamannyeleng, Barombong District, Gowa Regency. This research is a qualitative research with a descriptive approach. The subjects in this study are the supervisor, the chairman of the committee, and 3 high-class teachers. The data collection techniques in this study use interviews, observations, and documentation while the data analysis techniques used include data reduction, data presentation, and conclusion drawn/verification. The results of the study show that the policy of the head of SD Inpres Tamannyeleng to improve the pedagogic and professional competence of teachers includes training, development, mentoring, and impact evaluation, supported by strong management, adequate resources, and stakeholder cooperation. Obstacles such as lack of support, limited access to training, and lack of funding are overcome through strengthening leadership, expanding access, and effective fund management. For the quality of science and technology learning, the policy includes planning, structured training, and monitoring, supported by facilities, teacher competence, and partnerships. Obstacles in the form of limited facilities and community support are overcome by intensive training, facility improvement, and community collaboration. This comprehensive policy is expected to significantly improve the quality of education.